Iron Bioavailability from a Lipid-Based Complementary Food Fortificant Mixed with Millet Porridge Can Be Optimized by Adding Phytase and Ascorbic Acid but Not by Using a Mixture of Ferrous Sulfate and Sodium Iron EDT - Cercamondi, Colin I.; Egli, Raoul; MITCHIKPE, COMLAN EVARISTE SIMON; Tossou, FÉLICIEN; Hessou, Joamel; Zeder, Christophe; HOUNHOUIGAN, DJIDJOHO JOSEPH; Hurrell, Richard F. (My University, 2013)
Home fortification with lipid-based nutrient supplements (LNSs) is a promising approach to improve bioavailable iron and energy intake of young children in developing countries. To optimize iron bioavailability from an LNS named complementary food fortificant (CFF), 3 stable isotope studies were conducted in 52 young Beninese children. Test meals consisted of millet porridge mixed with CFF and ascorbic acid (AA). Study 1 compared iron absorption from FeSO4-fortifed meals with meals fortified with a mixture of FeSO4 and NaFeEDTA. Study 2 compared iron absorption from FeSO4-fortifed meals without or with extra AA. Study 3 compared iron absorption from FeSO4-fortified meals with meals containing phytase added prior to consumption, once without or once with extra AA. Iron absorption was measured as erythrocyte incorporation of stable isotopes. In study 1, iron absorption from FeSO4 (8.4%) was higher than that from the mixture of NaFeEDTA and FeSO4 (5.9%; P < 0.05). In study 2, the extra AA increased absorption (11.6%) compared with the standard AA concentration (7.3%; P < 0.001). In study 3, absorption from meals containing phytase without or with extra AA (15.8 and 19.9%, respectively) increased compared with meals without phytase (8.0%; P < 0.001). The addition of extra AA to meals containing phytase increased absorption compared with the test meals containing phytase without extra AA (P < 0.05). These findings suggest that phytase and AA, and especially a combination of the two, but not a mixture of FeSO4 and NaFeEDTA would be useful strategies to increase iron bioavailability from a CFF mixed with cereal porridge.
Keywords: Lipid-based complementary food fortificant; iron bioavailability; stable isotope; enhancers of iron absorption; Benin